Effectively Evaluating Online Faculty - David Line Denali; Mary-Katherine Smith; Stephen F Pyle (Academic Chairpersons Conference Proceedings, 2016)
Online courses and instructors require administration to use innovation to create valid faculty evaluations. This session examines why teaching evaluations need to be adjusted and how to make those adjustments to in order to effectively evaluate the faculty and therefore, keep administration, promotion committees, and faculty content.
Keywords: Creating Valid Online Faculty Evaluation